108 W average power ultrashort pulses with GW-level peak power from a Tm-doped fiber CPA system - Wang, Ziyao; Heuermann, Tobias; Gebhardt, Martin; Gaida, Christian; Jauregui, Cesar; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Applications such as material processing, spectroscopy, particle acceleration, high-harmonic and mid-IR generation can greatly benefit from high repetition rate, high power, ultrafast laser sources emitting around 2 μm wavelength. In this contribution we present a single-channel Tm-doped fiber chirped-pulse amplifier delivering 108 W of average output power at 417 kHz repetition rate with 250 fs pulse duration and 0.73 GW of pulse peak power. To the best of our knowledge, this is the first demonstration of an ultrafast Tm-doped fiber laser with more than 100 W of average power and GW-level peak power.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Short-wavelength mid-infrared; Thulium fiber laser; Ultrafast laser